Effect of promoting current local research activities on large monitors on the population's interest in health-related research: a randomised controlled trial. Issue 8 (1st August 2019) - Gunnarsson, Ronny; Cullen, Paul; Heal, Clare; Banks, Jennifer
Abstract : Objective: The objectives of this study were threefold: to estimate people's interest in health-related research, to understand to what extent people appreciate being actively informed about current local health-related research and to investigate whether their interest can be influenced by advertising local current health-related research using large TV monitors. Design: Randomised controlled trial using a stepped wedge design. Setting: The emergency department waiting room at two public hospitals in northern Queensland, Australia. Participants: Waiting patients and their accompanying friends and relatives in the emergency department waiting room not requiring immediate medical attention. Interventions: A TV monitor advertising local current health-related research. Main outcome measures: OR for the effect of intervention on changing the interest in health-related research compared with a control group while adjusting for gender, age and socioeconomic standard. Results: The intervention significantly increased the short-term interest in health-related research with an OR of 1.3 (1.1–1.7, p=0.0063). We also noted that being female and being older was correlated to a higher interest in health-related research Conclusions: This study found that proactive information significantly increased the general populations' interest in health-related research. There are reasonable set up costs involved but the costs for maintaining the system were very low. Hence, it seems reasonable that research-active organisations should give much higher priority to this type of activity. Trial registration number: ACTRN12617001085369